Low-cost thermal mechanical treatment method for improving yield strength of austenite light TWIP steel

Through the three-step thermal mechanical treatment method of solid solution-cold rolling-aging, the problem of low yield strength of austenite lightweight TWIP steel is solved, and the combination of high yield strength and high plasticity is achieved, reducing energy consumption and cost is expanded. Its application scope.

CN119287113APending Publication Date: 2025-01-10NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411484908.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The yield strength of austenitic lightweight TWIP steel is less than 800MPa. Traditional solid solution aging treatment has problems such as long aging time, high energy consumption and brittle precipitation phases.

Method used

Using the three-step thermal mechanical treatment method of solid solution-cold rolling-aging, the nano-ordered domain or second phase is introduced through cold rolling, combined with low-temperature aging treatment to improve yield strength, and at the same time, TWIP during plastic deformation is controlled Retention of effects.

Benefits of technology

It significantly improves the yield strength of austenitic lightweight TWIP steel to above 1150MPa, and retains high plasticity, reduces energy consumption and costs, and expands its application range in the automotive industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287113A_ABST
    Figure CN119287113A_ABST
Patent Text Reader

Abstract

The invention discloses a low-cost thermal mechanical treatment method for improving the yield strength of austenite light TWIP steel, which comprises the following steps: firstly, carrying out solution treatment on an austenite light TWIP steel material, and carrying out water quenching to room temperature; then the austenite light TWIP steel material subjected to solution treatment is subjected to cold rolling treatment at the room temperature; and finally, the austenite light-weight TWIP steel material subjected to cold rolling treatment is heated to 550-650 DEG C for aging treatment for 10 minutes and is subjected to water quenching to the room temperature, and dislocation with the density not lower than 1.94 * 10 < 15 > m <-2 > is generated in an austenite matrix of the austenite light-weight TWIP steel material. The invention relates to a method for preparing austenitic light TWIP steel, which comprises the following steps of: uniformly dispersing and distributing L '12 type long-range ordered domains with the average size of 1.15-1.48 nm and the volume fraction of 22-26%, and nano twin crystals with the average thickness of not more than 3.50 nm, the average spacing of 4.53-5.14 nm and the volume fraction of 2.7-6.9%, so that the yield strength of the austenitic light TWIP steel is obviously improved, reasonable plasticity (the elongation at break is more than 15%) is retained, and the method is simple to operate, low in energy consumption and cost and suitable for industrial production. And the application range of the austenite light TWIP steel in the field of automobile industry is expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lightweight steel, and in particular relates to a low-cost thermomechanical treatment method for improving the yield strength of austenitic lightweight TWIP steel. Background Art

[0002] After more than a century of vigorous development, the automobile industry has become a pillar industry for economic development in major industrial countries. In view of the prominent energy shortage problem, the automobile industry has an increasingly urgent need for energy conservation and emission reduction. The lightweighting of the body structure is an important way to improve fuel efficiency and achieve energy conservation and emission reduction. Therefore, the research and development of lightweight structural materials for automobiles is crucial to the development of the automobile industry. In 2000, Georg Frommeyer and Udo Brüx of the Max Planck Institute for Iron Research in Germany proposed the concept of using Fe-Mn-Al-C lightweight steel for automobile manufacturing, which attracted widespread attention. After nearly 20 years of development, lightweight steel has become an important structural material for automobiles, and its application range is still expanding. According to the different phase compositions, lightweight steel can be subdivided into several categories, including ferritic lightweight steel, ferritic dual-phase lightweight steel, austenitic dual-phase lightweight steel and austenitic lightweight steel. Among them, austenitic lightweight steel can introduce twinning induced plasticity (TWIP) effect during deformation by regulating the stacking fault energy, thereby obtaining high work hardening ability and high plasticity, so it has attracted much attention.

[0003] However, the yield strength of austenitic lightweight steels with obvious TWIP effect is usually lower than 800MPa, which greatly limits its application in the automotive field. In order to break through this strength limitation, a large number of related studies are currently focused on improving the yield strength of such lightweight steels by precipitating nano-ordered domains or second phases through aging treatment. However, this method has two limitations: on the one hand, during low-temperature aging treatment, the formation rate of nano-ordered domains or second phases is slow, and it usually takes several hours or even dozens of hours of aging to achieve the expected strengthening effect, which inevitably leads to a significant increase in energy consumption and cost; on the other hand, although increasing the aging temperature can accelerate the formation rate of nano-ordered domains or second phases, it is also easy to cause coarse brittle precipitation phases at the austenite grain boundaries, which can easily cause a significant deterioration in plasticity.

[0004] Based on this, the present invention proposes a low-cost thermomechanical treatment method for improving the yield strength of austenitic lightweight TWIP steel. Summary of the invention

[0005] In view of the problem that the existing austenitic lightweight TWIP steel generally has a low yield strength (less than 800MPa), considering that the traditional solid solution aging treatment can improve its yield strength by precipitating nano-ordered domains or second phases, it has the limitations of too long time, high energy consumption and cost for low-temperature aging, and easy generation of brittle precipitation phases during high-temperature aging, which leads to plasticity deterioration. Cold rolling can introduce a large number of dislocations and accelerate the precipitation of nano-ordered domains or second phases during the aging process, thereby significantly improving the yield strength while reducing energy consumption and cost. Therefore, designing a reasonable thermomechanical treatment method combining solid solution, cold rolling and aging is the key way to solve the problem of low yield strength of existing austenitic lightweight TWIP steel in a low-cost manner.

[0006] Based on the above considerations, the present invention proposes a low-cost thermomechanical treatment method for improving the yield strength of austenitic lightweight TWIP steel, which specifically includes the following steps: Step 1: subjecting the austenitic lightweight TWIP steel material to a solid solution treatment and then water quenching to room temperature; obtaining a fully recrystallized γ-austenite equiaxed crystal structure, wherein there are uniformly dispersed L12-type long-range ordered domains in the γ-austenite, and the average size of the L12-type long-range ordered domains does not exceed 1.05 nm and the volume fraction does not exceed 20%, so as to ensure that it has good room temperature deformation ability and is convenient for subsequent cold rolling treatment; Step 2: The austenitic lightweight TWIP steel material after solution treatment is cold rolled at room temperature; the volume fraction of the L12 type long-range ordered domain in the obtained γ austenite is not more than 12%, so as to provide enough formation sites for the generation of L'12 type long-range ordered domains in the subsequent aging treatment process; the average thickness of the nanotwins generated in the γ austenite is not more than 3.64nm, the average spacing is not less than 2.75nm, the volume fraction is not less than 8.2%, and the dislocation density in the γ austenite is not less than 5.87×10 15 m -2 , to ensure that there are enough dislocations in the subsequent aging treatment process to provide a sufficiently large driving force to accelerate the formation of L'12 type long-range ordered domains; Step 3: The austenitic lightweight TWIP steel material after cold rolling is heated to 550℃~650℃ for aging treatment for 10 minutes, and then quenched to room temperature; the L12-type long-range ordered domain in the obtained γ austenite is transformed into the L'12-type long-range ordered domain, and the L'12-type long-range ordered domain is uniformly dispersed, and its average size is 1.15nm~1.48nm, and the volume fraction is 22%~26%, so as to ensure that the TWIP effect in the plastic deformation process is not completely suppressed while the yield strength of the material is significantly improved, so that it retains a sufficiently high plasticity, the average thickness of the nanotwins in the γ austenite is not more than 3.50nm, the average spacing is 4.53nm~5.14nm, and the volume fraction is 2.7%~6.9%, so as to ensure that the material has a sufficiently high dislocation storage capacity, so as to retain a sufficiently high dislocation density, and the dislocation density in the γ austenite is not less than 1.94×10 15 m -2 , to ensure that the dislocation strengthening effect makes a sufficiently high contribution to the improvement of the material's yield strength.

[0007] Preferably, the solution treatment temperature in step 1 is 1000°C to 1200°C, which can avoid the generation of α ferrite and grain boundary κ* carbides that are not conducive to the plasticity of the material due to too low a temperature, and can prevent the material from melting due to too high a temperature. The solution treatment time is not less than 45 minutes to ensure that the material is fully recrystallized.

[0008] Preferably, the cold rolling treatment in step 2 is carried out on a double-roll strip mill, and the cold rolling process includes multiple rolling processes with small deformation amounts, and the deformation amount of each pass is not higher than 5% to avoid cracking of the rolled plate due to excessive single deformation. The total deformation amount is 72%~77% to ensure that enough nanotwins and dislocations are introduced into the material.

[0009] Preferably, the solution treatment in step one and the aging treatment in step three are both carried out in a resistance furnace in an argon atmosphere.

[0010] Preferably, the heating method for the solution treatment in step one and the aging treatment in step three is to charge to temperature.

[0011] Preferably, during the water quenching process, the interval between the austenitic lightweight TWIP steel material being taken out of the heat treatment furnace and being placed in water is within 60 seconds.

[0012] Preferably, the alloy used in the austenitic lightweight TWIP steel is a fully recrystallized γ-austenite equiaxed crystal structure, and most of the grains contain annealing twins; the average grain size of the solid solution alloy is about 103 μm when the twin boundaries are not included, and the average grain size of the solid solution alloy is about 49 μm when the twin boundaries are included; the dislocation density in the γ-austenite is about 1.39×10 13 m-2 .

[0013] Compared with the prior art, the present invention has the following beneficial effects: The present invention overcomes the shortcomings of the traditional solution aging method, such as long aging time, high energy consumption and easy generation of coarse brittle precipitation phase, by rationally designing each link of the three-step thermomechanical treatment of solution-cold rolling-aging. By simply combining a simple cold rolling treatment and an aging treatment for 10 minutes, a density of not less than 1.94×10 15 m -2 The dislocations, as well as the L'12 type long-range ordered domains with an average size of 1.15nm~1.48nm and a volume fraction of 22%~26% uniformly dispersed in the γ austenite matrix and the nano twins with an average thickness of no more than 3.50nm, an average spacing of 4.53nm~5.14nm, and a volume fraction of 2.7%~6.9%, significantly improve its yield strength to more than 1150MPa, and retain reasonable plasticity (fracture elongation greater than 15%). The thermomechanical treatment method provided by the present invention is an important way to improve the yield strength of austenitic lightweight TWIP steel, and it is simple to operate and low in cost, which is conducive to expanding the application scope of austenitic lightweight TWIP steel in the automotive industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 1 is the transmission electron microscopy characterization result of the ordered domain of the austenitic lightweight TWIP steel after solution treatment provided in Example 1 of the present invention, wherein (a) is the selected area electron diffraction pattern, (b) is the bright field image, and (c) is Figure 1 (b) Enlarged image of the selected area; Figure 2 The transmission electron microscopy characterization results of the ordered domains of the austenitic lightweight TWIP steel after cold rolling provided in Example 1 of the present invention, wherein (a) is a selected area electron diffraction pattern, (b) is a bright field image, and (c) is Figure 2 (b) Enlarged image of the selected area; Figure 3 is the XRD spectrum of the austenitic lightweight TWIP steel provided in Example 1 of the present invention after cold rolling; Figure 4 1 is the transmission electron microscopy characterization result of dislocation and twinning of the austenitic lightweight TWIP steel after cold rolling provided by Example 1 of the present invention, wherein (a) is a bright field image, (b) is a dark field phase of microbands, and (c) is a dark field phase and selected area electron diffraction pattern of twinning; Figure 5 1 is the transmission electron microscopy characterization result of the ordered domain of the austenitic lightweight TWIP steel after aging treatment provided in Example 1 of the present invention, wherein (a) is the selected area electron diffraction pattern, (b) is the bright field image, and (c) is Figure 5 (b) Enlarged image of the selected area; Figure 6 is the XRD spectrum of the austenitic lightweight TWIP steel after aging treatment provided in Example 1 of the present invention; Figure 7 1 is the transmission electron microscopy characterization result of dislocation and twinning of the austenitic lightweight TWIP steel after aging treatment provided in Example 1 of the present invention, wherein (a) is a bright field image, (b) is a dark field phase of microbands, and (c) is a dark field phase and selected area electron diffraction pattern of twinning; Figure 8 It is a tensile engineering stress-engineering strain curve diagram of the austenitic lightweight TWIP steel in Examples 1-2 of the present invention and Comparative Examples 1-2. DETAILED DESCRIPTION

[0015] In order to make the purpose, technical solution and advantages of the embodiments of the present disclosure clearer, the technical solution of the embodiments of the present disclosure will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the described embodiments of the present disclosure, all other embodiments obtained by those skilled in the art without creative work also fall within the scope of protection of the present disclosure.

[0016] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by those skilled in the art to which the subject matter of the present disclosure belongs. It will be further understood that terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning in the context of the specification and the relevant art, and will not be interpreted in an idealized or overly formal form unless otherwise explicitly defined herein.

[0017] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase "embodiments" in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments. Example 1

[0018] The austenitic lightweight TWIP steel forging blank used in the present invention is selected as the raw material, and a sample is taken from the forging blank to perform the following thermomechanical treatment: S1. The sample was heated to 1050℃ for solution treatment, kept at this temperature for 45 minutes and then quenched to room temperature to obtain a completely recrystallized γ-austenite equiaxed crystal structure, and there were L12-type long-range ordered domains with an average size of 0.97 nm and a volume fraction of 17% uniformly distributed in the grains (see Appendix Figure 1 as shown).

[0019] S2. Use a twin-roll strip mill to perform multiple passes of small deformation cold rolling on the solution treated sample at room temperature. The deformation of each pass is not more than 5%, and the total deformation is 75%, so that the volume fraction of the L12 type long-range ordered domain in the γ austenite is reduced to 12% (see Appendix). Figure 2 As shown), the density reaches 5.87×10 15 m -2 The dislocation (caused by the attached Figure 3 The XRD patterns of the nanotwins are as follows: Figure 4 as shown).

[0020] S3. The cold-rolled sample was heated to 550°C for aging treatment, kept at this temperature for 10 minutes, and then quenched to room temperature, so that L'12 type long-range ordered domains with an average size of 1.15 nm and a volume fraction of 22% were uniformly dispersed in the γ austenite (see attached Figure 5 As shown in the figure), the density of γ austenite is retained to be 3.05×10 15 m -2 The dislocation (caused by the attached Figure 6 The XRD patterns of the nanotwins are as follows: Figure 7 as shown).

[0021] The solution treatment and aging treatment are both carried out in a resistance furnace with an argon atmosphere; the heating method for the solution treatment and aging treatment is to charge the sample at temperature; during the water quenching treatment, the interval between taking the sample out of the heat treatment furnace and putting it into water is limited to within 60 seconds.

[0022] The mechanical properties of the austenitic lightweight TWIP steel samples treated in this embodiment were measured in accordance with GB / T 228.1-2010 "Tensile testing of metallic materials - Part 1: Room temperature test methods". The results are shown in the attached figure. Figure 8 As shown, its yield strength is 1248MPa, tensile strength is 1385MPa, and elongation at break is 17%. Example 2

[0023] The austenitic lightweight TWIP steel billet used in the present invention is selected as the raw material, and samples are taken from the forging billet for the following thermomechanical treatment: S1. The sample was heated to 1060℃ for solution treatment, kept at this temperature for 45 minutes and then quenched to room temperature to obtain a completely recrystallized γ-austenite equiaxed crystal structure. In addition, there were L12-type long-range ordered domains with an average size of 1.05 nm and a volume fraction of 20% uniformly dispersed in the grains.

[0024] S2. The solution treated sample was subjected to multiple cold rolling with small deformation at room temperature using a twin-roll strip mill. The deformation of each pass was no more than 5%, and the total deformation was 75%. The volume fraction of the L12 long-range ordered domain in the γ austenite was reduced to 15%, and the density was 5.93×10 15 m -2 dislocations, and nanotwins with an average thickness of 3.52nm, an average spacing of 2.93nm, and a volume fraction of 8.2%.

[0025] S3, the sample after cold rolling was heated to 650℃ for aging treatment, kept at this temperature for 10 minutes and then quenched to room temperature, so that the L'12 type long-range ordered domains with an average size of 1.48nm and a volume fraction of 26% were uniformly dispersed in the γ austenite, and the retention density in the γ austenite was 1.94×10 15 m -2 dislocations, and nanotwins with an average thickness of 3.42nm, an average spacing of 5.14nm, and a volume fraction of 2.7%.

[0026] The solution treatment and aging treatment are both carried out in a resistance furnace with an argon atmosphere; the heating method for the solution treatment and aging treatment is to charge the sample at temperature; during the water quenching treatment, the interval between taking the sample out of the heat treatment furnace and putting it into water is limited to within 60 seconds.

[0027] The mechanical properties of the austenitic lightweight TWIP steel samples treated in this embodiment were measured in accordance with GB / T 228.1-2010 "Tensile testing of metallic materials - Part 1: Room temperature test methods". The results are shown in the attached figure. Figure 8 As shown, its yield strength is 1193MPa, tensile strength is 1375MPa, and elongation at break is 22%.

[0028] Comparative Example 1 The austenitic lightweight TWIP steel billet used in the present invention is selected as the raw material, and samples are taken from the forging billet for the following heat treatment: S1. Heat the sample to 1050℃ for solution treatment, keep it at this temperature for 45 minutes and then quench it to room temperature.

[0029] S2. Heat the solution treated sample to 550°C for aging treatment, keep it at this temperature for 10 minutes, and then quench it to room temperature.

[0030] The solution treatment and aging treatment are both carried out in a resistance furnace with an argon atmosphere; the heating method for the solution treatment and aging treatment is to charge the sample at temperature; during the water quenching treatment, the interval between taking the sample out of the heat treatment furnace and putting it into water is limited to within 60 seconds.

[0031] The mechanical properties of the austenitic lightweight TWIP steel samples treated in this embodiment were measured in accordance with GB / T 228.1-2010 "Tensile testing of metallic materials - Part 1: Room temperature test methods". The results are shown in the attached figure. Figure 8 As shown, its yield strength is 341MPa, tensile strength is 724MPa, and elongation at break is 73%.

[0032] Comparative Example 2 The austenitic lightweight TWIP steel billet used in the present invention is selected as the raw material, and samples are taken from the forging billet for the following thermomechanical treatment: S1. Heat the sample to 1050℃ for solution treatment, keep it at this temperature for 45 minutes and then quench it to room temperature.

[0033] S2. Use a double-roll plate and strip mill to perform multiple passes of small deformation cold rolling on the sample after solid solution heat treatment at room temperature. The deformation of each pass is not more than 5%, and the total deformation is 75%.

[0034] The solution treatment and aging treatment are both carried out in a resistance furnace with an argon atmosphere; the heating method for the solution treatment and aging treatment is to charge the sample at temperature; during the water quenching treatment, the interval between taking the sample out of the heat treatment furnace and putting it into water is limited to within 60 seconds.

[0035] The mechanical properties of the austenitic lightweight TWIP steel samples treated in this embodiment were measured in accordance with GB / T 228.1-2010 "Tensile testing of metallic materials - Part 1: Room temperature test methods". The results are shown in the attached figure. Figure 8 As shown, its yield strength is 1262MPa, tensile strength is 1385MPa, and elongation at break is 7%.

[0036] Compared with Examples 1-2, although the same austenitic lightweight TWIP steel material was used and the same solution and aging treatment was performed, Comparative Example 1 was not properly cold rolled before the aging treatment, which resulted in its strength being significantly lower than 1150 MPa. Compared with Examples 1-2, although the same austenitic lightweight steel forging billet was used and the same solution and cold rolling treatment was performed, Comparative Example 2 was not aged, and its thermomechanical treatment system was not within the scope of protection of this application, which resulted in its elongation at break being only 7%.

[0037] It should be noted that, in this article, terms such as "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.

[0038] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A low-cost thermomechanical treatment method for improving the yield strength of austenitic lightweight TWIP steel, characterized in that: The method comprises the following steps: Step 1: subjecting the austenitic lightweight TWIP steel material to a solid solution treatment and then water quenching to room temperature; obtaining a fully recrystallized γ-austenite equiaxed crystal structure, wherein there are uniformly dispersed L12-type long-range ordered domains in the γ-austenite, and the average size of the L12-type long-range ordered domains does not exceed 1.05 nm, and the volume fraction does not exceed 20%; Step 2: cold rolling the austenitic lightweight TWIP steel material after solid solution treatment at room temperature; the volume fraction of the L12 type long-range ordered domain in the obtained γ austenite is not more than 12%, the average thickness of the nano twins generated in the γ austenite is not more than 3.64nm, the average spacing is not less than 2.75nm, the volume fraction is not less than 8.2%, and the dislocation density in the γ austenite is not less than 5.87×10 15 m -2 ; Step 3: The austenitic lightweight TWIP steel material after cold rolling is heated to 550℃~650℃ for aging treatment for 10 minutes, and then quenched to room temperature; the L12-type long-range ordered domain in the γ austenite is transformed into the L'12-type long-range ordered domain, and the L'12-type long-range ordered domain is uniformly dispersed, and its average size is 1.15nm~1.48nm, and the volume fraction is 22%~26%. The average thickness of the nanotwins in the γ austenite is not more than 3.50nm, the average spacing is 4.53nm~5.14nm, and the volume fraction is 2.7%~6.9%. The dislocation density in the γ austenite is not less than 1.94×10 15 m -2 .

2. A low-cost thermomechanical treatment method for improving the yield strength of austenitic lightweight TWIP steel according to claim 1, characterized in that: The solution treatment temperature in step 1 is 1000° C. to 1200° C., and the solution treatment time is not less than 45 minutes.

3. A low-cost thermomechanical treatment method for improving the yield strength of austenitic lightweight TWIP steel according to claim 1, characterized in that: The cold rolling process in step 2 is carried out on a double-roll strip mill, and the cold rolling process includes multiple small deformation rolling processes, the deformation of each pass is not higher than 5%, and the total deformation is 72%~77%.

4. A low-cost thermomechanical treatment method for improving the yield strength of austenitic lightweight TWIP steel according to claim 1, characterized in that: The solution treatment in step 1 and the aging treatment in step 3 are both carried out in a resistance furnace with an argon atmosphere.

5. A low-cost thermomechanical treatment method for improving the yield strength of austenitic lightweight TWIP steel according to claim 1, characterized in that: The heating method for the solution treatment in step 1 and the aging treatment in step 3 is to charge the material at the temperature.

6. A low-cost thermomechanical treatment method for improving the yield strength of austenitic lightweight TWIP steel according to claim 1, characterized in that: During the water quenching treatment, the interval between the austenitic lightweight TWIP steel material being taken out of the heat treatment furnace and being placed in water is within 60 seconds.

7. A low-cost thermomechanical treatment method for improving the yield strength of austenitic lightweight TWIP steel according to claim 1, characterized in that: The alloy used in the austenitic lightweight TWIP steel is a fully recrystallized γ-austenite equiaxed crystal structure, and most of the grains contain annealing twins. In the case of no twin boundaries, the average grain size of the solid solution alloy is about 103 μm, and in the case of twin boundaries, the average grain size of the solid solution alloy is about 49 μm. The dislocation density in the γ-austenite is about 1.39×10 13 m -2 .